Path analysis on the Determinants of Pap Smear Utilization for Cervical Cancer Early Detection in Women of Reproductive Age - Gesit Kusuma Wardhani; Ambar Mudigdo; Isna Qadrijati (Journal of Health Promotion and Behavior, 2017)
Background: Cervical cancer is the fourth most common malignant cancer among women after breast, colorectal, and lung cancers. Pap smear has been recognized as an effective strategy for reducing the incidence and mortality rate of cervical cancer. This study aimed to investigate the determinants of Pap smear utilization for cervical cancer early detection in women of reproductive age using path analysis model.Subjects and Method: This was an analytic observational study with a case-control design. The study was conducted in Cilongok and Ajibarang Sub-districts, Banyumas, Central Java, from January 3 to February 3, 2018. A total sample of 200 women reproductive age was selected for this study by fixed disease sampling. The dependent variable was Pap smear utilization. The independent variables were education level, attitude, perception on the quality health care, access to the health center, family support, peer support, and health personnel support.  The data were collected by questionnaire and analyzed by path analysis.Results: Pap smear utilization was positively and directly associated with education (b = 2.63; 95% CI= 1.77 to 3.48 p<0.001), perception on quality of health care (b= 1.04; 95% CI= 0.22 to 1.86; p= 0.012), attitude (b= 1.48; 95% CI= 0.51 to 2.44 p= 0.003), access to health center (b=1.02; 95% CI= 0.20 to 1.84 p= 0.015), family support (b= 1.29; 95% CI= -0.22 to 2.61; p= 0.029), and health personnel support (b= 2.02; 95% CI= 0.60 to 3.45 p= 0.005). Pap smear utilization was indirectly associated with peer support through perception on quality health care (b = 0.66; 95%= -0.01 to 1.33 p = 0.031).Conclusion: Education, perception on the quality of health care, attitude, access to the health center, family support, and health personnel support are directly associated with Pap smear utilization.Keywords: Pap smear, cervical cancer, path analysis, education, attitude, perception, family support, peer support, health personnel supportCorrespondence: Gesit Kusuma Wardhani. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami No. 36 A, 57126, Surakarta, Central Java. Email: gesitkusuma92@gmail.com.Journal of Health Promotion and Behavior (2017), 2(4): 359-370https://doi.org/10.26911/thejhpb.2017.02.04.08